2006
DOI: 10.1021/jp0634048
|View full text |Cite
|
Sign up to set email alerts
|

Protic Ionic Liquids:  Solvents with Tunable Phase Behavior and Physicochemical Properties

Abstract: The phase behavior, including glass, devitrification, solid crystal melting, and liquid boiling transitions, and physicochemical properties, including density, refractive index, viscosity, conductivity, and air-liquid surface tension, of a series of 25 protic ionic liquids and protic fused salts are presented along with structure-property comparisons. The protic fused salts were mostly liquid at room temperature, and many exhibited a glass transition occurring at low temperatures between -114 and -44 degrees C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

53
514
2
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 486 publications
(580 citation statements)
references
References 48 publications
53
514
2
11
Order By: Relevance
“…In fact, it is in agreement with the estimation of 5.3Å based on the molar volume by Atkin and Warr [17].…”
Section: Laxs Experimentssupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, it is in agreement with the estimation of 5.3Å based on the molar volume by Atkin and Warr [17].…”
Section: Laxs Experimentssupporting
confidence: 92%
“…From the viewpoint of physico-chemical properties of EAN as liquid and/or solvent, its conductivity [15][16][17][18]21], viscosity [18,19], density [18,20,21] and phase transitions [18,21] have been reported. In addition, the acid-base property was discussed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…That calculated value is similar to σ m for a non-aqueous organic mixture when calculated using a simple binary approach, σ m =X acid σ acid +X base σ base . Experimental data have shown that measured σ m values for ionic liquids are typically greater than that for non-ionic organic liquids but less than that for pure water (Greaves et al, 2006). For dilute aqueous organic salt solutions, the presence of amines and NH 3 tends to lower surface tension (Mmereki et al, 2000;Donaldson, 1990), while the presence of an inorganic acid and subsequent salt formation increases surface tension (Weissenborn, 1996).…”
Section: Volatility Of Organic Acids and Dimethylamine Inmentioning
confidence: 99%
“…(Iglesias et al, 2004;Omotowa et al, 2004;Philips & Rabinski, 2004;Reich et al, 2003) Protic ionic liquids are a subset of ionic liquids formed by the stoichiometric (equimolar) combination of a Bronsted acid with a Bronsted base. (Greaves et al, 2006;Greaves & Drummond, 2008;Yoshizawa et al, 2003) Relevant investigations into the molecular interactions of carboxylic acids and amines were conducted by Kohler et al, and the complexes of acid and amine with the molecular ratio of 1:1 can be found. (Kohler, 1981a(Kohler, , 1981b) Ionic liquids, which possess an octadecyl ammonium salt with pentadecafluoro octanate, significantly reduce the friction compared to the corresponding amide and Z-DOL.…”
Section: Tape Drive Systemsmentioning
confidence: 99%